Synergy of oncolytic adenovirus and immune checkpoint inhibitors: transforming cancer immunotherapy paradigms - Cheng, Chong; Wang, Qingzhe; Zhang, Shuang (Frontiers in Immunology, 2025)
Oncolytic viruses (OVs) offer a promising antitumor strategy by selectively lysing tumor cells and simultaneously activating innate and adaptive immune responses. Recent studies have shed light on the immunostimulatory mechanisms of OVs, particularly oncolytic adenovirus (OAds), which are emerging as leading candidates due to their favorable safety profile, genomic stability, and efficient transduction capacity. Despite the significant progress made by immune checkpoint inhibitors (ICIs) in antitumor therapy, treatment resistance continues to be a major barrier to their clinical effectiveness. OVs and ICIs work synergistically: OVs reprogram the immunosuppressive tumor microenvironment (TME) through immune cell recruitment and pro-inflammatory cytokine production, potentially overcoming ICI resistance. In turn, ICIs enhance T cell function by blocking inhibitory signaling pathways. This review highlights recent preclinical and clinical advancements in the therapeutic potential of combining OAds with ICIs, while also addressing critical translational challenges. We propose a strategic framework for optimizing the development and clinical trial design of these combination therapies to advance precision immunotherapy.